Isolation, screening and characterization of cellulosic-utilizing bacteria - Coronel, Leticia; Joson, Lydia M. (1986)
Cellulose-degrading aerobic and mesophilic bacteria were isolated from soils of sugar cane fields and decaying organic matter by enrichment culture technique and modified screening procedures. Primary screening test of the isolates was done by visual determination and by using solid medium containing carboxymethylcellulose (CMC) to detect Cx cellulase activity. In the secondary screening test using liquid medium containing 1% cellulose in shaken cultures, 2 bacteria identified as Cellulomonas biazotea and C. gelida gave the highest filter paper and CMC-saccharifying activities.
Includes bibliographical references (pages 227-228)
Keywords: Biological Sciences; Bacteria, Cellulose degrading -- Isolation and identification; Cellulomonas biazotea; Cellulomonas gelida